Existência e Multiplicidade de Soluções Positivas para Algumas Classes de Problemas Envolvendo o p-Laplaciano - Araújo, Yane Lísley Ramos (2012)
In this work, using variational methods and the sub and super solutions method we study the existence and multiplicity of positive solutions for some classes of problems involving the p-Laplacian operator in bounded domains of RN. Initially, we study a result of existence of positive solution for a problem where the nonlinearity does not satisfy the classical Ambrosetti-Rabinowitz condition, and then we study the existence and multiplicity result of positive solutions for a class of problems where the considered nonlinearity can change sign.